1. DEXMEDETOMINDE AND KETAMIN COMBINATION FOR SPONTANEOUS SEDATION OF PEDIATRIC PATIENTS UNDERGOING CARDIAC CATHETERIZATION: INITIAL OUTCOME IN VIETNAM NATIONAL CHILDEN’S HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Initial assessment of the effectiveness and safety of combining Dexmedetomodine and Ketamin in spontaneous sedation for pediatric patients with congenital heart disease requiring cardiac catheterization.Research subjects and methods: Cohort, observational study from June 1, 2024 to July 31, 2024 on pediatric patients with congenital heart disease was indicated for cardiac catheterization. Combined with intravenous injection of Dexmedetomidine 2 mg/kg over 10 minutes, Ketamin 1 mg/kg; maintain by injected Dexmedetomidine 2 µg/kg/h and Ketamin 1 mg/kg/h, titrate depending on the patient's response to achieve the goal of spontaneous breathing sedation with a Ramsay level of 6, anesthesia with local anesthesia. Observe the influence of the drug on the level of sedation during intervention, heart rate, mean blood pressure, breathing rate, end-tidal CO2 concentration, oxygen saturation in peripheral blood, Stewards scale during recovery and unwanted effects.Results: A total of 32 patients from 4 months to 16 years old were included in the study, 60% had heart failure from grade III or higher, average cardiac catheterization time was 100.09 ± 51.68 (40-250) minutes, average anesthesia time was 121.18 ± 53.30 (55-280) minutes. There were 7/32 cases of sinus bradycardia that required treatment with atropine, of which 3 cases were due to catheter stimulation, and 3 cases were bradycardia in the recovery room. No patient had an increase or decrease in BP to the level that required treatment. The changes in respiratory indices were all within allowable limits, no patient required respiratory support. Time the patients were awake when called 85.20 ± 34.32 (10-160) minutes; time the patients were spontaneous eye opening 105.46 ± 54.55 (15-320) minutes, 34% of patients added Ketamin due to movement during intervention but no patient had to be transferred to general anesthesia; only 1 patient had nausea/vomiting in the recovery room, in addition, no other unwanted effects were observed.Conclusion: The combination of Dexmedetomidine and Ketamin in cardiac catheterization in children has a good sedative effect, maintains the patient's spontaneous breathing and is safe.
Keywords: Dexmedetomidine - Ketamin; spontaneous sedation; pediatric; cardiac catheterization